Manufacturing parameters and entrepreneurship space consideration - Sharma, Sanjay, Dr. (Boca Raton, FL : CRC Press, 2021)
Manufacturing Parameters and Entrepreneurship provides a guide that helps business leaders understand and apply the production parameters and estimation techniques needed for commercial success. This book covers important concepts in depth, including manufacturing space, manufacturing quality, production backorders, space consideration, quality aspects, maximum inventory control, entrepreneurial application, and quality inclusion. Key features: Covers manufacturing parameters, their estimation, and effects in a single volume. Discusses conceptualization, formulation, and analysis of space consideration. Provides basic understanding and mathematical treatment of quality aspects in detail. Discusses in detail concepts such as manufacturing space, manufacturing quality, and production backorders. Covers stock out situations in detail. Manufacturing Parameters and Entrepreneurship will be an invaluable addition to the libraries of graduate students and professionals in the field of industrial engineering, production engineering, and manufacturing science and engineering.
OCLC-licensed vendor bibliographic record.
Keywords: Production engineering; Production management; TECHNOLOGY / Industrial Design / General; TECHNOLOGY / Manufacturing; TECHNOLOGY / Industrial Technology